Prowincja jako centrum - Kledzik, Emilia (Wydawnictwo-Drukarnia Bonami/Pracownia Komparatystyki Literackiej IFP UAM, 2008)
Recenzja książki: Provinz als Zentrum. Regionalität in Literatur und Sprache. Ein polnisch-deutsch-nordisches Symposium. Red. D. Albrecht, A. Degen, B. Neumann, A. Talarczyk. Aachen 2007, ss. 226.

Review of book: Provinz als Zentrum. Regionalität in Literatur und Sprache. Ein polnisch-deutsch-nordisches Symposium. Red. D. Albrecht, A. Degen, B. Neumann, A. Talarczyk. Aachen 2007, ss. 226.
Province as centre
Keywords: Prowincja; Province; Centrum; Center; Europejskie regiony; European regions; Literatura wobec prowincji; Literature on the background of province